Development of early-flowering Kabuli chickpea with compound and simple leaves - Bonfil, D.; Goren, O.; Mufradi, I.; Lichtenzveig, Judith; Abbo, S. (John Wiley and Sons, 2007)
Terminal drought is a major constraint to chickpea (Cicer arietinum L.) production. Autumn sowing and early flowering have been suggested as ways to benefit from the winter rains in short rainy seasons under dryland cropping. High-yielding, late-flowering, simple-leafed (slv/slv) chickpea cultivars with good field resistance to Ascochyta blight have been bred recently. Changing plant architecture, by altering leaf shape, may affect agronomic performance. As no information is available on the effect of leaf shape on phenology and seed yield, this study was aimed at: (i) introducing the simple leaf trait into an early-flowering chickpea background; (ii) comparing the grain yield of the two leaf types in early vs. late flowering backgrounds and (iii) producing breeding lines combining early flowering, large seeds and Ascochyta tolerance with both leaf types. Hybrid progeny were studied from the cross of ‘Sanford’ (slv/slv) and ICC7344, (compound, SLV/SLV). Four early-podding, F8 breeding lines were selected with either simple or compound leaves. In three different field experiments under dryland conditions (334–379 mm), they yielded ca. 1.4 t/ha as compared with 1.0 t/ha in the standard Israeli ‘Yarden’ on one site, but no significant differences in yield were obtained in the other two experiments.